Energy Expenditure and Intensity of Cheerleading Training: A Descriptive Study - Ulloa Sánchez, Paul (2021)
The objective of the present study was to answer the following questions: are the energy expenditure equivalent in terms of METs of cheerleading training sessions and what Ainsworth et al. (2011) show? Are there statistically significant differences in the energy expenditure and intensity of cheerleading training when comparing different performance and sex categories? Methodology: Energy expenditure and intensity were measured during one hour of cheerleading training for a sample of 103 cheerleaders (men = 55; women = 48), who belong to three all-star teams and two national teams from Costa Rica. Results: No differences were found between the value reported by Ainsworth et al. (2011) and cheerleading workouts (6 METs vs. 5.8 METs, t = -1.7, p = 0.092). A significant interaction of energy expenditure (kcal) between sex and performance category was evident. Conclusions: The energy expenditure in terms of METs for cheerleading workouts is equivalent to that reported by Ainsworth et al. (2011). Men with a “high” performance category had significantly higher energy expenditure (p <0.05 *) compared to men with a “medium” or “low” category and with women in all three categories. No differences were found in terms of intensity when comparing sex and performance category.